PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK MATERI DAERAHKU KEBANGGANKU UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD - Salimi, Ma'isyatus; Rahmawati, Ery; Wahju Andjariani, Endang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the problem, namely the use of media that still does not attract students' interest in learning, causing low student learning outcomes. This research aims to improve student learning outcomes by developing interesting learning media in the form of comics. The subjects of this study were grade V elementary school students. The method used in this study is using the Research and Development method based on the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The research techniques used are validation and testing. Research findings show that the feasibility rate of learning media that has been validated by media experts is 95.2% and is included in the very feasible category. Analysis of learning outcomes used the validity of the questions with a score of 92.3% and was included in the decent category, and the learning outcomes of students with the N-Gain test obtained a score of 0.721 so that they were included in the High category. Based on the results of development research, the development of comic learning media in science subjects is my proud area to improve the learning outcomes of grade V elementary school students.